Robust Structural Design against Self-Excited Vibrations - Spelsberg-Korspeter, Gottfried; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book studies methods for a robust design of rotors against self-excited vibrations. The occurrence of self-excited vibrations in engineering applications if often unwanted and in many cases difficult to model. Thinking of complex systems such as machines with many components and mechanical contacts, it is important to have guidelines for design so that the functionality is robust against small imperfections. This book discusses the question on how to design a structure such that unwanted self-excited vibrations do not occur. It shows theoretically and practically that the old design rule to avoid multiple eigenvalues points toward the right direction and have optimized structures accordingly. This extends results for the well-known flutter problem in which equations of motion with constant coefficients occur to the case of a linear conservative system with arbitrary time periodic perturbations.
Perturbation of a linear conservative system by periodic parametric excitation -- Eigenvalue placement for structural optimization -- Passive stabilization of discrete systems -- Passive stabilization in continuous systems -- Structural optimization of a disk brake -- Nonlinear analysis of systems under periodic parametric excitation.
Keywords: Engineering; Vibration; Engineering design; Engineering; Vibration, Dynamical Systems, Control; Engineering Design